MINTAQAVIY ENERGIYA TA'MINOTI TIZIMLARINI TAKOMILLASHTIRISHNING ZAMONAVIY YONDASHUVLARI (Marketing Journal, 2026)
AbstractThis article analysed modern models for optimizing regional energy supplysystems. The study conducted a comparative evaluation of linear programming,stochastic optimization, and hybrid models based on artificial intelligence. Energyefficiency indicators of Uzbekistanʼs regions were assessed using statistical data.Differences in regional energy supply efficiency were identified and optimizationresults were evaluated. Opportunities for integrating renewable energy sources into theenergy system were examined based on international data sources. The role of SmartGrid technologies and IoT sensors in energy distribution management was analysed.The findings demonstrated that hybrid AI-based models improved the efficiency ofregional energy systems. The results were considered as a practical basis for improvingregional energy management and optimization strategies.Keywords: energy system optimization, Smart Grid, renewable energy, artificialintelligence, regional energy efficiency, hybrid models.